Differential role of afferent and efferent renal nerves in the maintenance of early- and late-phase Dahl S hypertension - Foss, Jason D. (Am J Physiol Regul Integr Comp Physiol, 2015)
Clinical data suggest that renal denervation (RDNX) may be an effective treatment for human hypertension; however, it is unclear whether this therapeutic effect is due to ablation of afferent or efferent renal nerves. We have previously shown that RDNX lowers arterial pressure in hypertensive Dahl salt-sensitive (S) rats to a similar degree observed in clinical trials. In addition, we have recently developed a method for selective ablation of afferent renal nerves (renal-CAP). In the present study, we tested the hypothesis that the antihypertensive effect of RDNX in the Dahl S rat is due to ablation of afferent renal nerves by comparing the effect of complete RDNX to renal-CAP during two phases of hypertension in the Dahl S rat. In the early phase, rats underwent treatment after 3 wk of high-NaCl feeding when mean arterial pressure (MAP) was ∼140 mmHg. In the late phase, rats underwent treatment after 9 wk of high NaCl feeding, when MAP was ∼170 mmHg. RDNX reduced MAP ∼10 mmHg compared with sham surgery in both the early and late phase, whereas renal-CAP had no antihypertensive effect. These results suggest that, in the Dahl S rat, the antihypertensive effect of RDNX is not dependent on pretreatment arterial pressure, nor is it due to ablation of afferent renal nerves.